(untitled) (International Journal of World Civilizations and Philosophical Studies, 2024)
This article will focus on the continuation of the philosophy of modernism that supports modern liberalism to the philosophy of postmodernism that is growing in the Eastern world including Malaysia. The modernism philosophy developed in the West during the renaissance era which was later applied to the countries colonized by the Western countries including Malaysia. However, some Western philosophers consider that the liberalism philosophy is no longer relevant. As a response, the existence postmodernism is a philosophy that arose in response to the liberalism philosophy. Postmodernism began in the west in the 1940s but only began to develop as a philosophy in the 1970s by figures such as Lyotard and Foucault. Postmodernism emphasizes thinking that focuses on the issue of absolute truth. This article will discuss the history of the development of postmodernism and its development in Eastern countries, especially in Malaysia, as well as the continuity with the previous philosophy, which is liberalism philosophy that developed in the era of modernism